2017
DOI: 10.1016/j.clgc.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of c-Met Expression and Outcome in Patients With Renal Cell Carcinoma Treated With Sunitinib

Abstract: High c-Met expression was associated with poor survival in patients with mRCC treated with sunitinib. Interestingly, the prognostic role may vary based on the location of metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…In a descriptive analysis, we observed that patients in our cohort who were treated with VEGF-TT and had high c-Met expression had numerically worse clinical outcomes, in terms of reduced TTF and OS, compared to those patients treated with VEGF-TT who had low c-Met expression. While our small sample size limited formal statistical testing, our findings are consistent with other data showing that high c-Met expression portends worse clinical prognosis [ 5 , 7 , 9 , 14 , 15 ]. Furthermore, we observed that patients treated with VEGF-TT in between the resection of their primary RCC and subsequent metastasis had numerically higher c-Met expression in metastatic sites compared to those who did not receive systemic therapy before the resection of the metastases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a descriptive analysis, we observed that patients in our cohort who were treated with VEGF-TT and had high c-Met expression had numerically worse clinical outcomes, in terms of reduced TTF and OS, compared to those patients treated with VEGF-TT who had low c-Met expression. While our small sample size limited formal statistical testing, our findings are consistent with other data showing that high c-Met expression portends worse clinical prognosis [ 5 , 7 , 9 , 14 , 15 ]. Furthermore, we observed that patients treated with VEGF-TT in between the resection of their primary RCC and subsequent metastasis had numerically higher c-Met expression in metastatic sites compared to those who did not receive systemic therapy before the resection of the metastases.…”
Section: Discussionsupporting
confidence: 90%
“…In RCC, high c-Met expression was reported to be an independent predictor of survival in 330 nephrectomy cases using quantitative immunofluorescence [ 6 ]. In the metastatic RCC (mRCC) setting, c- Met expression also appears to be associated with worse outcomes in a retrospective cohort of patients treated with sunitinib, an antiangiogenic agent against vascular endothelial growth factor receptor (VEGFR) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In RCC, many studies have suggested that c-Met expression is associated with significantly inferior clinicopathological features, such as tumor grade [ 27 , 28 31 , 36 , 38 ], primary tumor stage [ 30 , 31 , 36 ], lymphatic invasion [ 27 ], metastases [ 30 , 35 , 38 ], and worse progression-free survival [ 37 ] or OS [ 31 , 34 , 36 ]. However, the pathological or clinical impacts of c-Met expression are not consistent across the studies [ 33 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…1) [24,25]. Принципиальным отличием кабозантиниба от TKI 1-го поколения (сунитиниб, пазопаниб, сорафениб, акситиниб) является способность блокировать MET и AXL, гиперэкспрессия которых ассоциирована с плохим прогнозом и резистентностью к противоопухолевой терапии при раке почки [26,27]. В образцах рака почки, рефрактерного к сунитинибу, кабозантиниб ингибировал экспрессию AXL и MET [28].…”
Section: механизм действия кабозантинибаunclassified